Spectrophotometric Method for the Estimation of Total Alkaloids in the Stem Bark of Symplocos racemosa and in Its Formulations - KUMAR, G.S.; SANJAY UMACHIGI, P.; VRUSHBENDRA SWAMY, B.M.; DHANAPAL, R.; ASHOK KUMAR, C.K.; JAYVEERA, K.N. (Asian Journal of Chemistry, 2010)
A simple sensitive, precise, reproducible and accurate UV/ Visible spectrophotometric method of estimation of alkaloids in stem bark of Symplocos racemosa (Lodhra) and in its formulations using tropaeolin ‘OO’ was developed. The method was found suitable for alkaloids bound to tannins causing interference in the analysis process. The method can be adopted as routine tool for standardization and quality control.